The Impact of Digital Comic-based Modules on Students’ Achievement in English Proficiency Test - Dias Tiara Putri Utomo; Finaty Ahsanah (Universitas Hamzanwadi, 2023)
Many students face difficulties in passing the English Proficiency Test (EPT) score of 450; whereas it is one of the graduation requirements students must meet. This study aimed to investigate the impact of digital comic-based modules on students’ English Proficiency Test (EPT) achievement. The modules were used during the EPT preparation class which was held for 16 meetings. This was pre-experimental research with one group pretest-posttest design. One hundred fifty-seven (157) undergraduate students from two different majors, Nursing and Computer Engineering participated in this study. The data were collected by administering pretest and posttest EPT which consisted of 140 questions in total. Then, the scores were analyzed statistically using paired-sample t-test and effect size. Based on the statistical analysis, the results showed an increase in students' EPT scores after learning EPT materials using digital comic-based modules. The increase in students’ EPT scores indicated an improvement in students’ understanding of the materials. Combining texts and images in digital comics provided students with contextual and meaningful learning. The existence of attractive features of digital comics also stimulated other factors including enthusiasm and interest. The transformation of conventional EPT modules to digital comics has made students feel more convenient and thus affected students’ comprehension. From this research, instructors and students are recommended to use digital comic-based modules in EPT preparation classes.